QSAR Study on Malate Dehydrogenase Inhibitors - Kumar Srivastava, Ravi; Prakesh Singh, Ved; Nath Dhar, Durga (Asian Journal of Chemistry, 2010)
Heat of formation, HOMO energy, total energy, absolute hardness, chemical potential, global hardness and energy of LUMO have been used as descriptors in different combinations, to develop quantitative structure activity relationship (QSAR) models of inhibitors of enzyme malate dehydrogenase. The inhibitors are derivatives of 7-substituted-4-hydroxyquinoline-3-carboxylic acids. Thirty QSAR models have been found to have high degree of predictive power with regression coefficient above 0.8 and six models above 0.876. The combination of descriptors providing best models are heat of formation, total energy alongwith any of two descriptors viz., HOMO energy, LUMO energy, absolute hardness and chemical potential.